Repeated Nash implementation - Claudio Mezzetti; Ludovic Renou (Theoretical Economics, 2017)
We study the repeated implementation of social choice functions in environments with complete information and changing preferences. We define dynamic monotonicity, a natural but nontrivial dynamic extension of Maskin monotonicity, and show that it is necessary and almost sufficient for repeated Nash implementation, regard less of whether the horizon is finite or infinite and whether the discount factor is 'large' or 'small.'
Keywords: C72; D71; 330; Dynamic monotonicity; Nash implementation; Maskin monotonicity; repeated implementation; repeated games